Aetiology of Ludwig’s Angina: A Hospital Based Study (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Ludwig’s angina is potentially life-threatening spreading cellulites of neck with high level of morbidity and mortality. Dental caries and diabetes mellitus are most common aetiological factor for Ludwig’s angina. Bad oral hygiene and poor socioeconomic condition are also responsible for this grave disease. This disease was frequently fatal; mortality rates for Ludwig’s angina exceeded 50% in the pre antibiotic era; however, antibiotics and aggressive surgical intervention have significantly reduced mortality recent series quote mortalities of 0-10%.  Objectives: To find out the aetiology of patient’s of Ludwig’s angina.Materials and Methods: This cross sectional descriptive study was conducted among 89 patients admitted in the Department of ENT and Head-Neck Surgery in Dhaka Medical College Hospital from 01.07.2010 to 30.06.2012. Patients were selected by specified inclusion and exclusion criteria. Data were collected in a structured questionnaire and analysed by SPSS 16.0 for Windows.Results: Among 89 patients about 69% were from rural area and55% from poor socio-economic class. Sixty-four patients (74.2%) suffered from dental caries and 15.7% were diabetic.Conclusion: Study shows some factors like dental caries, bad oral hygiene, oral mucosal infections, diabetes mellitus were associated with Ludwig’s angina, which may be preventable and curable by early diagnosis and intervention. The public awareness regarding aetiology of Ludwig’s angina may contribute great role in reduction of this disease prevalence.Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 81-83